A Literature Review of Voice Indices Available for Voice Assessment - Saeed Saeedi; Mahshid Aghajanzade; Ahmad Reza Khatoonabadi (Shiraz University of Medical Sciences, 2022)
Background:Recent years have seen the development of voice indices for multi-parametric objective voice evaluation. The current study aims to review these indices and examine their efficiency through the literature.Methods: The study design is a literature review. The five databases of 'PubMed', 'Scopus', 'Google Scholar', 'Science Direct', and 'Web of Science' were searched using the keywords 'voice index', 'acoustic', 'voice assessment', and 'acoustic analysis'. Attempts were made to include only the acoustic indices that have been validated and are fairly user-friendly.Results: Five voice indices were found that met the inclusion criteria: Dysphonia Severity Index (DSI), Acoustic Voice Quality Index (AVQI), Cepstral Spectral Index of Dysphonia (CSID), The Acoustic Breathiness Index (ABI), and Acoustic Psychometric Severity Index of Dysphonia (APSID).Conclusions: The results suggest using AVQI, ABI, DSI, and CSID in the evaluation and treatment of voice disorders. Of course, it is recommend to examine the efficacy of these indices in more languages and also developing new indices by considering more aspects of voice.